2020
DOI: 10.1021/acs.jnatprod.9b01020
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oxidative and Reductive Transformations in the Structure Determination of Marine Natural Products

Abstract: This review highlights the application of oxidative and reductive chemical transformations in the structure determination of complex marine natural products, including their absolute configurations. Workability of the Baeyer–Villiger reaction, ozonolysis, periodate oxidation, hydrogenolysis, and reductive amination, as well as other related chemical transformations, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The 40 carbon resonances in the 13 C NMR spectrum (Table 1, Fig. S11 in the ESI †) were classified using the HSQC spectrum into five carbonyl carbons (δ C 215.4, 215.2, 213.9, 206.2, and 173.8), four sp 3 methines, eighteen sp 3 methylenes (two oxygenated), one oxygen-bearing tertiary carbon (δ C 91.3), six sp 3 quaternary carbons, and six methyls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 40 carbon resonances in the 13 C NMR spectrum (Table 1, Fig. S11 in the ESI †) were classified using the HSQC spectrum into five carbonyl carbons (δ C 215.4, 215.2, 213.9, 206.2, and 173.8), four sp 3 methines, eighteen sp 3 methylenes (two oxygenated), one oxygen-bearing tertiary carbon (δ C 91.3), six sp 3 quaternary carbons, and six methyls.…”
Section: Resultsmentioning
confidence: 99%
“…of chemical transformations in the structural elucidation of complex natural products. [10][11][12][13][14] Biological assays revealed that compounds 1-7 showed moderate immunosuppressive effects against concanavalin A (ConA)-induced proliferation of T lymphocytes and lipopolysaccharide (LPS)-induced proliferation of B lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Peracetylation of a crude mixture containing 1 and rhizochalin (3) peracetates followed by separation using HPLC (YMC-Pack ODS-A column, EtOH-H 2 O, 80:20) gave mainly oceanalin B peracetate 1a. This peracetate was subjected to reductive ozonolysis (O 3 , then NaBH 4 ) followed by acetylation (Ac 2 O, pyridine) [12]. Two products were isolated by HPLC as a mixture and identified as peracetates 4 and 5, the same derivatives of oceanalin A [4] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ozonolysis without additional treatment to cleave the double bond in 1 supported the exact locations of the double bond and methoxy group. Ozonolysis was carried out in MeOH at −70 °C to yield the methyl ester of α-keto acid 5 , which was analyzed by (+)­HRMS/MS (ESI): [M + H] + calcd for [C 45 H 71 N 7 O 18 Cl] + m / z 1032.4539, found m / z 1032.4513 (Figure ).…”
mentioning
confidence: 80%